A Review on Development of Kek Lapis Sarawak's Machine - Mohamad Syamim, Hamsawi; Ana Sakura, Zainal Abidin; Shahrol, Mohamaddan; Rasli, Muslimen; Mohd Syahmi, Jamaludin; Nurul Izzati, Hashim; Nazreen, Junaidi (EDP Sciences, 2016)
Kek Lapis Sarawak is a beautifully decorated and flavorful cake that can be considered as the artwork of the Malays in Sarawak. There is an overwhelming demand of the Kek Lapis Sarawak in the market that consequently need for automation. This paper summarizes comprehensive reviewed patents of the current machine and journals which have similar functions and related to the current function of manual process of producing Kek Lapis Sarawak. Conceptual idea of the Kek Lapis Sarawak machine consists of three modules namely Depositor Module, Cooling and Pressing Module and Baking Module. Therefore, patents and journals that have similar functions with these modules are reviewed that look into its advantages. The disadvantages of the design also considered for future design. Hence, the crucial advantages of each module considered are namely improved production rates, increased of hygienic rating, easy to maintenance and portability of a design. The reviewed patents and journals can be considered for the development of Kek lapis Sarawak's machine with some improvisations are needed to meet up the specific requirements of the machine